(untitled) (American Journal of Islam and Society, 2007)
The Honourable Mr Stephane Dion, Leader of the Liberal party of Canada, M. Gilles Duceppe, chef de la Parti Bloc Quebecois, The Honourable Jack Layton, Leader of the NDP party, senators and parliamentarians, Mr. Arar and Dr. Mazigh, honored guests, or in likely more appropriate terms for this event, friends and fellow Canadians: Assalamu Alaykum. May you all be in Peace. Let me welcome you all with the greeting of Islam on behalf of the Canadian Muslim network; a network of Muslim organizations across Canada from BC to Alberta all the way to Ontario, Quebec and the Maritimes. The network was put in place to create an environment of collaboration and communication between Muslim organizations on issues of interest to Muslim Canadians nationally as well as to enhance communication and collaboration between Canadians of Muslim faith with Canadians of all other faiths. The list of names of the organizations in the network is at the back of your program (attached here as appendix), and I invite you to look at it in detail to appreciate the breadth of representation here tonight. This initiative is also supported by a multitude of other organizations that are also listed at the back. As you may expect civil liberties is high on our agenda. The Canadian Muslim Network is proud to have organized this incredible event to pay tribute to our cherished civil liberties in Canada, to recognize the massive effort that many in this room exerted to ensure we restore our civil liberties and protect them for the future of our children and to remind ourselves that while we have reasons to celebrate our recent successes, the road ahead is still long. We are here today to pay tribute to civil liberties in Canada. Canada is a country that was never defined by the colour of the skin of its people or their religion, rather Canada was always a country defined by its values. Canada ...